Biocompatible polymeric nanoparticles with exceptional gastrointestinal stability as oral delivery vehicles for lipophilic bioactives. (April 2019) - Hu, Qiaobin; Bae, Minkyung; Fleming, Erika; Lee, Ji-Young; Luo, Yangchao
Abstract: Poor stability in gastrointestinal (GI) tract is a major challenge for applications of natural biopolymer-based nanoparticles as oral delivery vehicles. In this study, chitosan was modified by grafting stearic acid on its backbone to improve its amphiphilicity. The polymeric nanoparticles were prepared using stearic acid-conjugated chitosan and sodium caseinate via ionic gelation and chemical crosslinking by glutaraldehyde and periodate oxidized dextran. The physicochemical properties and stability in simulated GI fluids were systematically studied to obtain the optimal nanoparticles with a diameter of 150 nm and homogeneous size distribution. The electron microscope images suggested the well-maintained nanoparticulate structure in simulated GI fluids. The non-cytotoxicity and internalization of the nanoparticles by Caco-2 cells were confirmed using fluorescence microscope. Successful encapsulation and sustained release of curcumin were demonstrated. The as-prepared polymeric nanoparticles hold promising features to be oral delivery vehicles to carry lipophilic bioactives for future applications in food and pharmaceutical industries. Graphical abstract: Highlights: Stearic acid-chitosan conjugate was prepared via a novel and eco-friendly method. The as-prepared polymeric nanoparticles have exceptional gastrointestinal stability. The non-cytotoxicity and cellular uptake of the nanoparticles were demonstrated. Curcumin was loaded into nanoparticles to explore the potential for oral delivery.